CARBON EMISSIONS, RENEWABLE ENERGY AND STOCK MARKET PERFORMANCE IN AFRICA - Yusuf Olatunji Oyedeko; Olusola Segun Kolawole; Babajide Olumuyiwa Owoniya; Samuel Lanrewaju Adetula (Malete Journal of Accounting and Finance)
This study examined the moderating role of renewable energy on the relationship between carbon emission and stock market performance in Africa. The study used secondary data and it is sourced from World Bank Development Indicator database for the period of 2000 to 2022. The descriptive statistics was used to describe the feature of the data and Panel VAR used as the estimating technique. It was found in the short run, that carbon emission and renewable energy have negative and insignificant effect on stock market performance in African. However, the interaction between the carbon emission and renewable energy has negative but insignificant effect on stock market performance. The introduction of the moderating term has reduced the negative effect of of carbon emission on stock market performance. However, the joint effect of carbon emission, renewable energy and the interaction between carbon emission and renewable energy can predict the stock market performance in Africa. It was concluded that there is no short run causality or influence running from carbon emission to stock market performance in the selected African countries. Thus, governments must invest in programs that enhance and promote renewable energy in African countries.